Innovating in nursing education: A brief review of literature - Sá, C.; Nabais, A.; Oliveira, A. (Proceedings of ICERI2019 Conference, 2019)
Nursing education has undergone many changes over the years. The development of new medical technologies challenges the present education systems to prepare nurses for the near future. The adoption and use of Information and Communication Technologies (ICT) is increasingly important for nursing teachers to be up to date with pedagogical advances, and prepare the nursing students with theoretical and technical-practical skills, through simulated situations, close to the reality of hospital units (where they'll be as professionals). The use of ICT in nursing education is essential to facilitate the acquisition of knowledge and, particularly, to promote competences, being a challenge both for teachers and students. Aim: The main goal of this paper is to Identify and analyse the innovation in nursing education, i.e., how nursing teachers use ICT in the teaching-learning process. Methodology: We started with the question research: How do nursing teachers use ICT in the teaching-learning process? Data sources were online databases, including CINHAL, MEDELINE and PUBMED. The selection of the articles for the present review was made according to the titles and the abstracts. The selected papers were analysed using a content analysis method. Results: Findings revealed that the teaching of future nurses in laboratories using advanced technologies, such as mannequins and equipment that provide realistic simulations, and the use of ICT facilities, facilitate the pedagogical process, both in classroom and through e-learning methods. Conclusion: The results from the different articles suggest that ICT promote knowledge for students and these information technologies are crucial in nursing education and a great challenge for the teachers, helping to train professionals prepared to deal with the technological scenarios they will encounter in health institutions.